Zambia : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents the Joint Staff Assessment of Zambia's Poverty Reduction Strategy Paper (PRSP) Progress Report. The report concludes that the implementation of the PRSP has been weaker than intended because of the extreme pressures placed on the budget by extrabudgetary expenditures, which reduced the funding available to PRSP programs and activities. The report also acknowledge that Zambia's economic program supported by the IMF's Poverty Reduction and Growth Facility arrangement has been off track since April 2003 owing to fiscal slippages, in particular salary and wage overrun, which led to high domestic borrowing.